2015
DOI: 10.1007/s11426-015-5511-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional architectures constructed using two-dimensional nanosheets

Abstract: Two-dimensional (2D) nanomaterials such as transition metal dichalcogenides (TMDs) and graphene have attracted extensive interest as emergent materials, owing to their excellent properties that favor their future use in electronic devices, catalysis, optics, and biological-or energy-relevant areas. However, 2D nanosheets tend to easily restack and condense, which weakens their performance in many of these applications. Assembling these 2D nanosheets as building blocks for three-dimensional (3D) architectures n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
0
16
0
1
Order By: Relevance
“…The assembled architecture of the nanosheets also plays an important role due to its strong correlation with the optoelectronic, electrical, magnetic, and thermal properties of nanosheet-based devices. [43][44][45] To date, very few studies have reported the effect of assembled architecture on electrochemical performance, since the rational control of the composition and morphology is very difficult to achieve. It is, therefore, highly desirable but also extremely challenging to develop a universal method to gradually manipulate the architecture of nanosheets with the goal of further improving their properties and functionalities in practical applications.…”
mentioning
confidence: 99%
“…The assembled architecture of the nanosheets also plays an important role due to its strong correlation with the optoelectronic, electrical, magnetic, and thermal properties of nanosheet-based devices. [43][44][45] To date, very few studies have reported the effect of assembled architecture on electrochemical performance, since the rational control of the composition and morphology is very difficult to achieve. It is, therefore, highly desirable but also extremely challenging to develop a universal method to gradually manipulate the architecture of nanosheets with the goal of further improving their properties and functionalities in practical applications.…”
mentioning
confidence: 99%
“…Driven by the reduction of surface energy, freestanding 2D NSs are subject to an inherent tendency of aggregation or restacking, [ 146 ] which can eliminate reactive sites and thus erode catalytic properties. [ 147 ] This drawback is resolved in 3D hierarchical architecture built from 2D NSs, in which the intrinsic advantages of 2D units are retained and new intriguing physicochemical properties arise. This section covers the recent progress in the synthesis of hierarchical 3D TMOs and TMCs.…”
Section: Hierarchical 3d Architecture From 2d Nssmentioning
confidence: 99%
“…Furthermore, such a 2D structure enables them to act as building blocks to be self‐assembled into various free‐standing architectures (e.g., film/paper and foam/sponge) with a continuous porous network by controlling the π–π stacking, van der Waals force, and electrostatic interaction between the planar basal planes. [ 16 ] These architectures display excellent mechanical properties and a highly conductive network since the continuous graphene scaffolds offer good electron/load transfer pathways. In addition, the pores of free‐standing architectures provide the space for loading sulfur and accommodating volumetric change.…”
Section: Free‐standing Architectures For Sulfur Cathodesmentioning
confidence: 99%